2020
DOI: 10.1016/j.neuropsychologia.2019.107328
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic internal states shape memory retrieval

Abstract: Why do we sometimes easily retrieve memories, but other times appear to forget them? We often look to our external environment for retrieval cues, but another way to optimize memory retrieval is to be in a mental state, or mode, that prioritizes access to our internal representation of the world. Such a 'retrieval mode' was proposed by Endel Tulving (1983), who considered it a neurocognitive state in which one keeps the goal of memory retrieval in mind. Building on Tulving's proposal, we review converging evid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 240 publications
(423 reference statements)
1
35
0
Order By: Relevance
“…As the vast majority of studies on MEAMs in healthy individuals examine only such spontaneously evoked memories (Belfi et al, 2016(Belfi et al, , 2020Jakubowski & Ghosh, 2019;Janata, 2009;Janata et al, 2007;Platz et al, 2015), the limits of music-evoked enhancements to memory retrieval are unknown. It is possible that music may invoke a 'retrieval mode' of increased attention to internal states and intention to retrieve memories (Tarder-Stoll et al, 2020). If familiar songs can particularly induce such a focus on retrieval, this could enhance both involuntary and voluntary recall of remote autographical episodes.…”
Section: What Kinds Of Memories Are Enhanced By Music?mentioning
confidence: 99%
“…As the vast majority of studies on MEAMs in healthy individuals examine only such spontaneously evoked memories (Belfi et al, 2016(Belfi et al, , 2020Jakubowski & Ghosh, 2019;Janata, 2009;Janata et al, 2007;Platz et al, 2015), the limits of music-evoked enhancements to memory retrieval are unknown. It is possible that music may invoke a 'retrieval mode' of increased attention to internal states and intention to retrieve memories (Tarder-Stoll et al, 2020). If familiar songs can particularly induce such a focus on retrieval, this could enhance both involuntary and voluntary recall of remote autographical episodes.…”
Section: What Kinds Of Memories Are Enhanced By Music?mentioning
confidence: 99%
“…This is consistent with the opposing behavioural and cognitive correlates of the theta and SWR states. High cholinergic levels in the hippocampus, promoting the theta state, favour externally driven sensory processing and engagement with the environment [103], whereas the lower cholinergic tone promoting the SWR state supports internally driven processes [104]. The low cholinergic state enhances intrinsic hippocampal dynamics, allowing internal connections to be reorganized and strengthened based on previously encoded associations [105].…”
Section: (A) Cholinergic Systemmentioning
confidence: 99%
“…Our work was inspired by studies that sought to test whether acetylcholine can toggle the hippocampus between externally and internally oriented states ( Tarder-Stoll, Jayakumar, et al, 2020 ). For example, computational modeling work and research with non-human animals has found that high levels of acetylcholine prioritize attention / encoding states in the hippocampus, while low levels of acetylcholine prioritize memory retrieval ( Easton et al, 2012 ;Hasselmo & Schnell, 1994 ;Hasselmo et al, 1996 ;Hasselmo & McGaughy, 2004 ;Meeter et al, 2004 ;Newman et al, muscarinic acetylcholine receptors impair new learning but do not affect recall of previously learned information ( Atri et al, 2004 ).…”
Section: Relation To Prior Workmentioning
confidence: 99%